Reticulon Protein-1C: A New Hope in the Treatment of Different Neuronal Diseases - Federica Di Sano; Mauro Piacentini (International Journal of Cell Biology)
Reticulons (RTNs) are a group of membrane proteins localized on the ER and known to regulate ER structure and functions. Several studies have suggested that RTNs are involved in different important cellular functions such as changes in calcium homeostasis, ER-stress-mediated cell death, and autophagy. RTNs have been demonstrated to exert a cancer specific proapoptotic function via the interaction or the modulation of specific proteins. Reticulons have also been implicated in different signaling pathways which are at the basis of the pathogenesis of several neurodegenerative diseases. In this paper we discuss the accumulating evidence identifying RTN-1C protein as a promising target in the treatment of different pathologies such as cancer or neurodegenerative disorders.